Effect of composition on the thermal behavior of NiMnGa alloys - Kok, Mediha; Aydogdu, Yildirim (Springer, 2013)
The methods to determine martensitic transformation temperature, enthalpy and entropy change, specific heat capacity change with temperature, and transformation activation energies of Ni-%29.5Mn-%21Ga, Ni-%29Mn-%21Ga, Ni-%29.5Mn-%20Ga, and Ni-%28.5Mn-%20.5Ga (atomic percentage) alloys were investigated by differential scanning calorimetry. It was observed that the transformation temperature increased with an increase in atomic nickel ratio. Meanwhile, it was detected that the change in enthalpy increases with the amount of nickel. The highest values of entropy change and the heat capacity at room temperature were observed in the alloy having the least amount of nickel in it.
Keywords: NiMnGa shape memory alloys; Thermal behavior; Entalpy change; Entropy change; Specific heat capacity